Condicionamento do solo com macrófitas aquáticas e biocarvão: 12 anos de recuperação de área severamente degradada no Cerrado - Alexandre, Joice Reali Oliveira [UNESP] (Universidade Estadual Paulista (Unesp), 2025)
This study evaluated the current state of recovery of an area severely degraded as a result of the construction of the Ilha Solteira Hydroelectric Plant in the Cerrado biome, 12 years after the first interventions for environmental recovery. The objective was to characterize the soil and vegetation conditions and verify the effectiveness of the techniques employed. The interventions included the application of aquatic macrophytes and biochar, derived from the burning of sugarcane bagasse, used as conditioners for severely degraded soil, using three doses of macrophytes (00, 16, and 32 t ha-1) and four doses of biochar (00, 15, 30, and 45 t ha-1), and the planting of seedlings of ten native Cerrado species, totaling 1,080 seedlings. After 12 years of interventions, the chemical and microbiological attributes of the soil were analyzed, as well as the survival and growth of the introduced tree species, soil cover by vegetation, and microclimatic indicators such as soil moisture and temperature. The results reveal that the area remains in the early stages of recovery. Among the introduced species, Hymenaea stigonocarpa (jatobá-do-cerrado) stood out for its high survival rate and good performance even without the addition of residues, indicating high tolerance to water stress and low fertility conditions, and may be recommended for projects to recover intensely degraded areas. However, most species had survival rates below 50%, compromising the formation of vegetation cover. The interaction between doses of aquatic macrophytes and biochar resulted in an increase in soil cover by spontaneous vegetation, about five times higher than the control, although the final value remained low (approximately 20%). This level of coverage is still insufficient to consistently modify soil moisture or temperature. Chemical analyses of the soil showed that biochar contributed to increasing pH, calcium and magnesium levels and reducing aluminum and potential acidity. Microbiological indicators show a trend toward increased microbial biomass and acid phosphatase activity with the introduction of aquatic macrophytes, but the effects of BC remain incipient, confirming that biological improvements in exposed soils occur slowly and depend on the gradual accumulation of organic matter. Water limitation was identified as one of the main obstacles to the recovery process, aggravated by the high exposure of the subsoil, conditions that hinder germination, seedling establishment, and microbial activity. Given this scenario, it is concluded that, although the practices applied have generated localized advances, the area still shows low indicators of ecological recovery. To accelerate the process, it is necessary to intensify the input of organic matter, increase the diversity of native species—including herbaceous plants and Cerrado grasses—and adopt management practices to improving water infiltration and retention in the soil.

Este trabalho avaliou o estado atual da recuperação de uma área severamente degradada em decorrência da construção da Usina Hidrelétrica de Ilha Solteira, no bioma Cerrado, doze anos após as primeiras intervenções para recuperação ambiental. O objetivo foi caracterizar as condições edáficas e da vegetação e verificar a eficácia das técnicas empregadas. As intervenções incluíram a aplicação de macrófitas aquáticas e biocarvão, oriundo da queima do bagaço da cana-de-açúcar, utilizados como condicionadores do solo severamente degradado, por meio de 3 doses de macrófitas (00, 16 e 32 t ha-1) e 4 doses de biocarvão (00, 15, 30 e 45 t ha-1), e o plantio de mudas de 10 espécies nativas de Cerrado, totalizando 1.080 mudas. Após 12 anos das intervenções, foram analisados atributos químicos e microbiológicos do solo, bem como a sobrevivência e o crescimento das espécies arbóreas introduzidas, o recobrimento do solo por vegetação e indicadores microclimáticos, como umidade e temperatura do solo. Os resultados revelam que a área permanece em estágio inicial de recuperação. Entre as espécies introduzidas, Hymenaea stigonocarpa (jatobá-do-cerrado) destacou-se pela elevada taxa de sobrevivência e bom desempenho mesmo sem a adição dos resíduos, indicando elevada tolerância a condições de estresse hídrico e baixa fertilidade, podendo ser indicada para projetos de recuperação de áreas intensamente degradadas. A maioria das espécies, no entanto, apresentou sobrevivência abaixo dos 50%, comprometendo a formação de cobertura vegetal. A interação entre as doses de macrófitas aquáticas e biocarvão resultou em aumento no recobrimento do solo por vegetação espontânea, cerca de cinco vezes superior ao controle, embora o valor final tenha permanecido baixo (aproximadamente 20%). Esse nível de cobertura ainda é insuficiente para modificar de forma consistente a umidade ou a temperatura do solo. As análises químicas do solo demonstraram que o biocarvão contribuiu elevando o pH e os teores de cálcio e magnésio e reduzindo alumínio e acidez potencial. Os indicadores microbiológicos mostram tendência de aumento da biomassa microbiana e da atividade da fosfatase ácida com a introdução das macrófitas aquáticas, mas os efeitos do biocarvão (BC) permanecem incipientes, confirmando que melhorias biológicas em solos expostos ocorrem de forma lenta e dependem do acúmulo gradual de matéria orgânica. A limitação hídrica foi identificada como um dos principais entraves ao processo de recuperação, agravada pela elevada exposição do subsolo, condições que dificultam germinação, estabelecimento de plântulas e atividade microbiana. Diante desse cenário, conclui-se que, embora as práticas aplicadas tenham gerado avanços localizados, a área ainda apresenta baixos indicadores de recuperação ecológica. Para acelerar o processo, é necessário intensificar o aporte de matéria orgânica, aumentar a diversidade de espécies nativas — incluindo herbáceas e gramíneas do Cerrado — e adotar manejos voltados à melhoria da infiltração e retenção de água no solo.
Soil conditioning with aquatic macrophytes and biochar: 12 years of recovery in a severely degraded area in the Cerrado
Keywords: Resíduos ambientais; Cinza; Subsolo exposto; Área de empréstimo; Environmental residues; Gray; Exposed subsoil; Borrow land